ANALYSIS OF FINANCIAL MANAGEMENT IN MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMEs) CENTER COFFEE JULL ARABICA LHOKSEUMAWE - Rusydi Abubakar; Anwar Puteh; T. Saifullah; Frengki Putra Ramansyah; Sri Suci Handayani Situmeang (Universitas Efarina, 2025)
This study aims to analyze financial management at the Jull Arabica Coffee Center Micro, Small, and Medium Enterprises (MSMEs) in Lhokseumawe City. Good financial management is an important factor in maintaining business continuity and development, especially for MSMEs that still face limited resources and accounting understanding. The research method used is a qualitative approach with a descriptive research type. Data were obtained through direct interviews with business owners, observations, and documentation related to MSME financial activities. The results of the study indicate that financial management at the Jull Arabica Coffee Center MSME has not fully implemented the principles of good financial management, such as systematic financial recording, separation of personal and business finances, and the preparation of periodic financial reports. This condition has the potential to hinder business decision-making and the long-term development of MSMEs. Therefore, it is necessary to improve the understanding and implementation of more structured financial management so that MSMEs can improve their financial performance and business competitiveness.